Protein secretion in Pseudomonas aeruginosa: molecular cloning and characterization of the xcp-1 gene. - Bally, M (1989)
Pleiotropic mutations (xcp) affecting the secretion of proteins in Pseudomonas aeruginosa have been previously characterized and mapped at three different loci on the chromosome. The xcp-1 gene, which is located at the 0-min region, was isolated from a genomic bank containing DNA from P. aeruginosa PAO1. The recombinant cosmid pLX25 complemented the xcp::Tn5-751 insertion mutation previously described. The xcp-1 gene was located on pLX25 by mapping the insertion point of transposon Tn5-751 and by deletion and subcloning analysis. The xcp-1 gene was expressed when transcription was initiated from a tac promoter, and a 26,000-dalton protein was identified in Escherichia coli minicells. The Xcp-1 protein was associated with the membrane fraction of E. coli. A 30-kilodalton outer membrane protein was also affected by the xcp::Tn5-751 mutation in P. aeruginosa. The possible correlation between Xcp-1 and this protein is discussed.